Factors in Parents’ Decision to Choose Music Lessons for Young Children Aged 0-5 Years - Pattananon , Nicha; Charoenmongcolkij, Siriluk (Journal of Roi Kaensarn Academi, 2024)
The objective of this research was to study factors in parents’ decision to choose music lessons for young children aged 0-5 years in Bangkok. This research used a mixed-method approach, using qualitative interviews with two teachers experienced in early childhood music education and quantitative data from questionnaires completed by 19 parents whose children had attended music courses. The results showed that parents in Bangkok highly prioritize the developmental benefits of music education, with intellectual and emotional growth receiving the highest ratings (4.79 each), followed closely by creativity (4.74) and concentration improvement (4.74). Practical considerations, including the convenience of the music school location (4.74) and flexible scheduling (4.68), also significantly influence decision-making. Additionally, parents value music education for fostering a lifelong love for music (4.32) and developing motor skills (4.47). Social and cultural factors have a more moderate influence. Peer behaviors (3.50), media exposure (3.11), and cultural or religious traditions involving music (2.89) are less critical. Secondary considerations include affordability (3.68) and specific skill acquisition (3.79), with parents prioritizing holistic development over these aspects. Interviews with parents and teachers revealed additional challenges. The interviews with music teachers revealed that the key factors influencing parents to continue their child’s music learning from age 0-5 years are their understanding of the developmental benefits of music for early childhood and their personal musical preferences. Parents who are educated about the positive impact of music on young children’s development and have a strong personal connection to music are more likely to support and encourage their child’s continued engagement with music.